Accuracy of percutaneous soft-tissue interventions using a multi-axis, C-arm CT system and 3D laser guidance. Issue 10 (October 2015) - Kostrzewa, Michael; Rathmann, Nils; Kara, Kerim; Schoenberg, Stefan O.; Diehl, Steffen J.
Highlights: We compared CBCT with MDCT guided needle placement in an abdominal phantom. Technical success, accuracy, and overall procedural time were evaluated. Overall procedural duration is in general shorter using MDCT guidance. MDCT and CBCT guidance showed comparable accuracy for in and off-plane interventions. CBCT-guided interventions offer the advantage of more degrees of freedom. Abstract: Introduction: Purpose of this phantom study was to compare the accuracy of needle placement using a multi-axis, C-arm-based, flat-panel, cone-beam computed tomography system (CBCT guidance) with that under multi-detector computed tomography guidance (MDCT guidance). Materials and methods: In an abdominal phantom, eight lesions (six lesions in the liver and two in the renal pelvises, respectively) were each punctured in-plane and off-plane with a 20G needle under CBCT and MDCT guidance. Access paths were initially defined and reproduced identically on the two systems. In total, 32 interventions were conducted. CBCT and MDCT guidance was compared prospectively with respect to technical success, accuracy, and overall procedural time. Results: All 32 interventions were technically successful in that it was possible to hit the respective lesion in each procedure. When comparing the accuracy of MDCT to CBCT guidance there was no significant difference in absolute, angular, and longitudinal deviation for either in- or off-plane interventions. Overall procedural duration was significantly longer under CBCT guidance for in-plane interventions (888 vs 527 s, p = 0.00005), whereas, for off-plane procedures there was no significant difference between CBCT and MDCT guidance (920 vs 701 s, p = 0.08). Off-plane interventions took significantly longer than in-plane interventions under MDCT guidance (701 vs 527 s, p = 0.03), whereas under CBCT guidance no significant difference could be found between off- and in-plane procedures (920 vs. 888 s, p = 0.2). Conclusions: In this phantom study, we could show that percutaneous soft-tissue interventions under CBCT guidance can be conducted with an accuracy comparable to that under MDCT guidance. Although overall procedural duration is in general shorter using MDCT guidance, CBCT-guided interventions offer the advantage of more degrees of freedom, which is of particular importance for off-plane procedures.